Ideal Educator for Generation Z Perspective of Al-Quran Surah An-Nahl Verse 43-44: Pendidik Ideal Bagi Generasi Z Perspektif Al-Quran Surah An-Nahl Ayat 43-44 - Viva Fadma Onilivia; Fatimah Jahroh; Rizqi Lestari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In the current era of technology, educators as educational subjects have very important functions and duties for the current generation, or what is usually called generation Z. Educators are role models and mentors who always lead to goodness and obedience to Allah. The ideal educator is an educator who is able to imitate and follow the teaching pattern of the Prophet as an educator. In Surah An-Nahl verses 43 and 44, it is explained that people who do not know something should ask an expert (ahlu dzikr), and it was revealed to Rasulullah ad-dzikr (al-Quran) to convey to humans what has been commanded so that humans think. This research uses a qualitative research approach with a library research method by looking for related sources such as books, articles, readings and so on. The application of Surah An-Nahl 43-44 to the role of educators is that they must be a source of knowledge or ahlu dzikr, must understand the main duties, functions and roles, must make the Messenger of Allah a role model, educators must be able to understand and practice the Al-Quran, and educators are a source of knowledge for students which includes words, actions and attitudes. The urgency of this discussion is to increase knowledge in the treasures of Islamic education from the perspective of the Al-Quran regarding ideal educators for the current generation Z.